2018
DOI: 10.1111/apa.14231
|View full text |Cite
|
Sign up to set email alerts
|

National population‐based cohort study found that visual‐motor integration was commonly affected in extremely preterm born children at six‐and‐a‐half years

Abstract: Poor VMI performance was common in this EXPRESS cohort of children born EPT. Its strong association to cognition and manual dexterity confirms that all of these factors need to be taken into account when evaluating risks in preterm born children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…An increasing body of research targeting the consequences of PT birth indicates cascading disruption to neurological development, [1][2][3][4][5][6] with the degree of deficits correlating with degree of prematurity. [7][8][9][10][11][12][13][14] Specifically, converging findings from animal models along with human neuroimaging investigations indicate that early disruption to white and gray matter development resulting from PT birth is largely responsible for inducing disruption of cognitive development [15][16][17][18][19] and psychopathologies. [20][21][22] Brain plasticity-the way experiences shape neural wiring of the brain-is thought to be one of the primary mechanisms through which humans adapt to environmental change and demonstrate resilience to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of research targeting the consequences of PT birth indicates cascading disruption to neurological development, [1][2][3][4][5][6] with the degree of deficits correlating with degree of prematurity. [7][8][9][10][11][12][13][14] Specifically, converging findings from animal models along with human neuroimaging investigations indicate that early disruption to white and gray matter development resulting from PT birth is largely responsible for inducing disruption of cognitive development [15][16][17][18][19] and psychopathologies. [20][21][22] Brain plasticity-the way experiences shape neural wiring of the brain-is thought to be one of the primary mechanisms through which humans adapt to environmental change and demonstrate resilience to adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…[25], and the foundations of the skills necessary for success in these activities emerge in early infancy. Fine motor execution and visual-motor integration is key for exploration and development of handwriting skills [10,26] and is particularly strongly associated with development of early working memory and mathematical abilities in early school age [7,27]. Children born EPT are at particularly high risk of school failure, disorders of executive functioning and mathematical disability at school age [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Precise, integrated hand muscle movement in early life is critical for exploration of the environment and communication with others. Further, fine motor functioning is a crucial component of visual-motor integration (VMI) [8,10]. Successful visual-motor integration involves integrating visual perceptional processing and fine motor ability and has been associated with academic performance in spelling, writing, reading, and mathematics [8,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2014 study on premature infants with low birth weights, it was found that at a corrected age of 18-24 months, children displayed developmental delays in multiple areas such as motor skills, cognition and language 5 . Furthermore, infants who are born prematurely or extremely prematurely, are at risk for later visual-motor integration and higher-order visual problems which impact on school-related tasks [6][7][8][9] . Traditionally, occupational therapy offered to premature infants addressed specific deficits such as abnormal muscle tone, decreased range of motion at specific joints or a developmental delay which could have multiple causes 10 .…”
Section: Introductionmentioning
confidence: 99%